Perlindungan Hukum terhadap Rahasia Dagangpada Pengrajin Batik Tradisional(Studi di Desa Wisata Kerajinan Batik Natural Desa JarumKecamatan Bayat, Kabupaten Klaten) - Zahra, Auria Noermy, Inayah, S.H., M.H, Arvie Johan, S.H., M.Hum (2016)
The purpose of this study is to analyze the legal protection of trade secrets in relation to the contract / agreement between the batik and batik entrepreneurs and to describe the kind of action that can be considered in violation of trade secrets. This research is a normative legal research that comes from the literature. Sources of data obtained from primary and secondary legal materials namely literature, observation and interviews with technical analysis using qualitative analysis. The results showed leakage of trade secret information is the negative impact that their efforts between the craftsmen of unfair competition, which occurs contestable markets by several craftsmen to hijack employee imitate competitors and competitor products. The action is considered a violation of trade secrets in employment contracts between employers and workers is the displacement of workers from the makers of one to the other craftsmen who have fulfilled the leakage of trade secret information, especially on points of information being leaked is confidential, there is no permission for the use of confidential information, and there is the loss caused by the use of confidential information without permission.